A consideration of the social commentary within D.H. Lawrence's novel The rainbow : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Miller, Raymond P (Massey University, 1971)
D.H. Lawrence's critical essay "Why The Novel Matters" contains the personal claim: "Nothing is important but life... For this reason I am a novelist... The novel is the book of life." 1 D.H. Lawrence, "Why The Novel Matters" D.H. Lawrence. Selected Literary Criticism (1956), ed. Anthony Beal, Mercury Books, London. 1961. pp. 104, 105. This claim is elaborated upon in "Morality And The Novel": "The business of art is to reveal the relation between man and his circumambient universe at the living moment... If we think about it, we find that our life consists in this achieving of a pure relationship between ourselves and the living universe about us." 2 D.H. Lawrence, "Morality and The Novel" D.H. Lawrence. Selected Literary Criticism pp. 108, 109. Arnold Kettle, writing in An Introduction to the English Novel suggests that The Rainbow contains within it a manifestation of these assertions. He contends: "The search, the passionate, desperate search of the characters of The Rainbow is to achieve personal relationships which make them at one with the universe." 3 Arnold Kettle, An Introduction to the English Novel Volume II (1953) Hutchinson University Library, London. 1965. p. 109. He adds to this contention his conviction that this novel is firmly grounded in reality, that within The Rainbow Lawrence is concerned with "actual human social issues". 4 ibid., p. 111. Some of these issues he then indicates: " ...there is the whole question of the relationship between work and personality; there is an examination of the social set-up of Cossethay and Beldover, the position of the squire and the vicar and the schoolmaster; there is the problem of industrialism, the significance of the canal and the railways and the pits; there is a great deal and from many points of view about the English educational system; there is the question of the impact of the English Midlands on the Polish émigrés; above all there is all that is implied in the phrase 'the emancipation of women'." 5
Keywords: Lawrence, D. H. 1885-1930; Political and social views